The relations between market guidance, product and process innovation, and organizational performance - Corrêa, Suelen; Guimarães, Julio Cesar Ferro de; Severo, Eliana Andréa; Cruz, Márcia Rohr da (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
To achieve a higher organizational performance is desirable to ensure the permanence and growth of companies. However, a business environment marked by rapid technological and market changes demands from companies new responses or a combination of different strategies. The purpose of this study was to verify the influence of market orientation on product and process innovation, as well as of these on organizational performance. For this, a survey was carried out, applied to managers and owners of companies in the state of Rio Grande do Sul, and the Structural Equations Modeling technique was used to analyze the data. We found positive and significant relationships among the constructs studied, and observed that process innovation contributes more to organizational performance than product innovation. Thus, business managers who seek to stay and grow on the market must invest more in process innovations than in product innovations, as they contribute to cost reduction and product quality enhancement, giving companies a superior organizational performance.